STMKu Application Design for Financial Management Transparency in STM Organizations - Ika Devi Perwitasari; Jodi Hendrawan; Fitri Yani Panggabean (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2023)
The STM organization is a social organization that aims to establish friendship, help each other in joy or sorrow among Muslims. another goal is to maintain neighborhood harmony and social relations between villagers in general, especially those who are Muslim. in supporting the implementation of its activities the STM organization collects and manages funds originating from several sources including mandatory contributions from members, member registration fees and other donations. in managing these funds, all expenses or income are recorded manually. This makes it difficult for the treasurer to report. Under these conditions, the process of financial reporting to members is considered not transparent. This of course can raise suspicions which will cause the harmony of neighbors to be disrupted. Therefore, the STMKu website was created which can be a medium of information for members and the public about financial management information and activities carried out by STM. STM management is also assisted in recording and reporting activities and financial processes. This application is made based on the website using the waterfall system development method.